Mutagenesis of N-terminal residues confer thermostability on a Penicillium janthinellum MA21601 xylanase - Ke Xiong; Jie Hou; Yuefeng Jiang; Xiuting Li; Chao Teng; Qin Li; Guangsen Fan; Ran Yang; Chengnan Zhang (BMC Biotechnology, 2019)
Abstract Background A mesophilic xylanase PjxA from Penicillium janthinellum MA21601 has high specific activity under acidic condition and holds great potential for applications in the animal feed industry. To enhance the thermostability of xylanase PjxA, two mutation strategies in the N-terminal region were examined and then integrated into the xylanase to further improvement. The recombinant xylanase PTxA-DB (The meaning of DB is disulfide-bridge.) was constructed by replacement of five residues in the mutated region in TfxA (T10Y, N11H, N12D, Y15F, N30 L), combined with an additional disulfide bridge in the N-terminal region. Results The T m value of mutant PTxA-DB was improved from 21.3 °C to 76.6 °C, and its half-life was found to be 53.6 min at 60 °C, 107-fold higher than the wild type strain. The location of the disulfide bridge (T2C-T29C) was between the irregular loop and the β-strand A2, accounting for most of the improvement in thermostability of PjxA. Further analysis indicated T2C, T29C, N30 L and Y15F lead to increase N-terminal hydrophobicity. Moreover, the specific activity and substrate affinity of PTxA-DB were also enhanced under the acidic pH values. Conclusions These results indicated PTxA-DB could be a prospective additive to industrial animal feeds.